Comparison of Long-term Cumulative Survival Rate and Standardized Mortality Ratio After Total Knee Arthroplasty in Patients with Rheumatoid Arthritis and Osteoarthritis - Yamashita F.,; Kobayashi M.,; Mizuno Y.,; Funakoshi N.,; Ito H.,; Mori D.,; Funakoshi H.,; Nishiyama H.,; Shirai T.,; Haku S.,; Shimozono Y.,; Tukasaki Y.,; et al. (Medical Research and Its Applications Vol. 8, 2024)
Background and Objective: Total knee arthroplasty (TKA) is an established surgical procedure that can relieve knee pain, enhance knee function, and improve the patient quality of life. The primary objective of this study is to clarify the long-term cumulative survival rate (CSR) and standardized mortality ratio (SMR) of rheumatoid arthritis (RA) and osteoarthritis (OA) patients who underwent total knee arthroplasty (TKA). Method: Data for 325 RA and OA patients with 460 primary TKAs from 1997 to 2007 were reviewed. We divided the patients into \(\le\)70 years (u70) and \(\ge\)71 years (o71) groups. The follow-up duration in the RA group (n=118) was 12.8±4.8 years vs 13.0±4.1 years in the OA group (n=207). The Cumulative Survival Rate was estimated using the Kaplan–Meier method. Results: The SMR of the female RA patients was 1.97 (95%CI 0.96-3.89) after 5 years and 4.59 (95%CI 3.44-6.10) after 20 years. The SMR in female OA patients was 0.41 (95%CI 0.17-0.93) after 5 years and 1.31 (95%CI 0.996-1.73) after 20 years. The 20-year CSR of female RA-o71 patients was lowest with 9.6 (95%CI 0-26). There was no significant difference in CSR between the RA-u70 and OA-o71 groups. The CSR in the OA-u70 group was highest with 77.8 (95%CI 0.62-0.93). Cox proportional hazards model analysis of female patients showed that steroid-use [Hazard ratio (HR) 3.22, 95%CI 1.32-13.46], age (HR 1.09, 95%CI 1.05- 1.30), and rheumatoid factor (HR 1.002, 95%CI 1.00-1.01) were risk factors in the RA-u70 group. In the RA-o71 group, steroid use (HR 4.71, 95%CI 1.35-16.7), age (HR 1.38, 95%CI 1.12-1.71) and C-reactive protein (HR 1.20, 95%CI 1.02-1.41) were risk factors, whereas in the OA group, only age at surgery (HR 1.10, 95%CI 1.033-1.163) was a risk factor. Conclusion: The study concluded that CSR was higher in patients with OA versus RA. SMR of female patients was high in RA and low after 5 years in OA. RA-u70 patients had a similar cumulative survival curve as OA-o71. The CSR of RA-o71 patients was poor. The preoperative factors affecting survival differed between u-70 and o-71 in RA.